2019
DOI: 10.1021/acs.jpcc.8b11253
|View full text |Cite
|
Sign up to set email alerts
|

Link of Weak Ferromagnetism to Emergence of Topological Vortices in Bulk Ceramics of h-LuMnxO3 Manganite

Abstract: Research on topological defects in hexagonal manganites exposed uncovered properties of topologically protected domains and domain walls. Topological defects of h-REMnO 3 oxides (RE = Lu−Dy and Sc, In) modify essential multiferroic properties. Despite wide research with single crystals of stoichiometric composition, for the case of polycrystalline ceramics rare studies explored the effects of adjustment in chemical composition on phase transition temperatures, antiferromagnetic ordering, topological domain siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…Topological phases, as a new phase of matter, have drawn intensive attention due to the ability to induce exotic states on the surfaces or edges of the material. , The states are extremely robust against defects and disorders because of the topology protection, giving rise to the outstanding characteristics. Hence, topological materials are creating a range of new opportunities throughout electronics and have promising applications in variously relevant areas including quantum information and quantum computation. , Distinct topological phases have been identified in various materials. Measurements have shown that three-dimensional (3D) topological materials exhibit spin-polarized 2D states on the surface, and 2D topological materials are quantum spin Hall insulators with novel 1D spin-polarized edge states. Spin polarization is closely related to the topological phases and plays a critical role in determining properties of various topological materials. , …”
Section: Introductionmentioning
confidence: 99%
“…Topological phases, as a new phase of matter, have drawn intensive attention due to the ability to induce exotic states on the surfaces or edges of the material. , The states are extremely robust against defects and disorders because of the topology protection, giving rise to the outstanding characteristics. Hence, topological materials are creating a range of new opportunities throughout electronics and have promising applications in variously relevant areas including quantum information and quantum computation. , Distinct topological phases have been identified in various materials. Measurements have shown that three-dimensional (3D) topological materials exhibit spin-polarized 2D states on the surface, and 2D topological materials are quantum spin Hall insulators with novel 1D spin-polarized edge states. Spin polarization is closely related to the topological phases and plays a critical role in determining properties of various topological materials. , …”
Section: Introductionmentioning
confidence: 99%